TI_GERICHTE 52.2014.295 vom 20. Juli 2015 , Segnaletica sperimentale: chiusura di un nucleo al traffico di transito - TI Tribunale d'appello (2015)
Segnaletica sperimentale: chiusura di un nucleo al traffico di transito